Appendectomy for Therapy-Refractory Ulcerative Colitis Results in Pathological Improvement of Colonic Inflammation: Short-Term Results of the PASSION Study. (3rd October 2018) - Sahami, S; Wildenberg, M E; Koens, L; Doherty, G; Martin, S; D'Haens, G R A M; Cullen, G; Bemelman, W A; Winter, D; Buskens, C J
Abstract: Background and Aims: The objective of this study was to examine the modulating effect of an appendectomy on the disease course of therapy-refractory ulcerative colitis [UC] patients, and to analyse appendiceal pathological characteristics predictive of pathological response. Methods: Patients with therapy-refractory UC, and referred for proctocolectomy, were invited to undergo laparoscopic appendectomy first. The primary end points were clinical response after 3 and 12 months. Secondary end points were endoscopic remission, failure, and pathologic response. Appendiceal specimens, and pre- and post-operative biopsies were histologically graded according to the validated Geboes score. Results: Thirty patients [53% male] with a median age of 40 (interquartile range [IQR], 33–47) underwent appendectomy, with a median preoperative total Mayo score of 9 [IQR, 8–11]. After 12 months, 9 patients [30%] had lasting clinical response, of whom 5 [17%] were in endoscopic remission. Pathological evaluation was possible in 28 patients. After a median of 13.0 weeks [range 7–51], pathological response was seen in 13 patients [46%], with a median decrease of 2 points [range 1–3]. Appendiceal inflammation was highly predictive of pathological response when compared with no inflammation or extensive ulcerations [85% vs 20%, p = 0.001]. Conclusions: Appendectomy was effective in one-third of therapy-refractory UC patients, with a substantial proportion of patients demonstrating complete endoscopic remission after 1 year. Pathological response was seen in almost 50% of patients and was related to active inflammation in the appendix, limited disease, and shorter disease duration. These early results suggest that there is a UC patient group that may benefit from appendectomy.